2011
DOI: 10.1016/j.phrs.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and health: An evidence-based review

Abstract: a b s t r a c tThe intestinal microbiota is an ecosystem formed by a variety of ecological niches, made of several bacterial species and a very large amount of strains. The microbiota is in close contact with the intestinal mucosa or epithelial interface which is, after the respiratory area, the largest surface of the body, occupying approximately 250-400 m 2 . The physiological activities of the microbiota are manifold and are just being unraveled. Based on the observations of the multiple roles played by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
135
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(145 citation statements)
references
References 123 publications
(113 reference statements)
1
135
0
9
Order By: Relevance
“…LAB have become the focus of probiotic research internationally and their health benefits in the prevention of diarrhoea (Hempel et al, 2012), reduction of the cholesterol level (Jones, Martoni, & Prakash, 2012), relief of both irritable bowel syndrome (Ducrotté, Sawant, & Jayanthi, 2012) and milk allergy in infants (Kekkonen et al, 2008) are well documented. However, these properties cannot be extrapolated or generalised for all probiotic strains as such effects are strain-specific and a considerable number of works are still required to affirm the benefits of each probiotic candidate (Aureli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAB have become the focus of probiotic research internationally and their health benefits in the prevention of diarrhoea (Hempel et al, 2012), reduction of the cholesterol level (Jones, Martoni, & Prakash, 2012), relief of both irritable bowel syndrome (Ducrotté, Sawant, & Jayanthi, 2012) and milk allergy in infants (Kekkonen et al, 2008) are well documented. However, these properties cannot be extrapolated or generalised for all probiotic strains as such effects are strain-specific and a considerable number of works are still required to affirm the benefits of each probiotic candidate (Aureli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria are generally regarded as safe since reports on the occurrence of harmful effects on humans is scarce (Leahy, Higgins, Fitzgerald, & Van Sinderen, 2005). The safety criteria established for the assessment of probiotics include the absence of unusual antibiotic resistant properties in the bacteria as this might create the possibility of transferring antibiotic resistant genes from probiotic plasmids to other bacteria, particularly pathogenic microorganisms (Aureli et al, 2011). It is also of great importance that the potential probiotics have the ability to survive through various industrial processes at elevated temperature during manufacturing of food products.…”
Section: Introductionmentioning
confidence: 99%
“…A number of different factors are able to affect the composition of the colonic microbiota, e.g. composition of the diet, aging, stress, health status, and environmental cicrcumstances (Aureli et al, 2011, Berg, 1996, Collins et al, 1998, Fooks et al, 1999, Guarner and Malagelada, 2003, Holzapfel and Schillinger, 2002. Selected strains of the lactic acid bacteria (LAB) belonging mainly to the genera Lactobacillus and Bifidobacterium have been used many years in the food production, predominantly in the manufacture of fermented dairy products and have GRAS (Generally Recognized As Safe) status (Collins et al, 1998, Dunne et al, 2001, Del Piano et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported health-promoting properties of lactic acid bacteria in animals and humans. These properties include: enhancing the bioavailability of minerals (calcium, iron, manganese, copper and phosphorus), synthesis of several vitamins (B and K groups), prevention and treatments of gastrointestinal disorders (diarrhea, gastrointestinal and urogenital infections), treatments of hypercholesterolaemia, and lactose intolerance, reduction in pro-carcinogenic enzymes, stimulation of the immune system, and treatment of food-re lated allergies (Aureli et al, 2011, Collins et al, 1998, Dalié et al, 2010, Fooks et al, 1999, Guarner and Malagelada, 2003, Holzapfel and Schillinger, 2002, Seale and Millar, 2013, Nomoto, 2005, Prescott and Björkstén, 2007, Saad et al, 2013, Salminen et al, 1998, Shah, 2007, Sullivan and Nord, 2002. Recently research suggests, that probiotics may have also anti-obesity effects (Kovatcheva-Datchary and Arora, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are often administered through functional fermented foods with the aim to increase their health and nutritional benefits. Probiotics are currently defined as live, orally administered bacteria, that have a positive influence on human health by improving their intestinal microbial balance, and that may have therapeutic effects (Aureli et al 2011).…”
mentioning
confidence: 99%